Parenting Patterns of Career Women in Instilling Islamic Religious Values in Children (Case Study of Communities in Griya Hangtuah Permai Housing, Pinang Kencana Kelurahan Tanjung Pinang Timur) - Hasnawati, Hasnawati; Suryanti, Ulya Maylani; Igiasi, Teguh Setiandika (Formosa Journal of Applied Sciences, 2024)
This research uses a descriptive qualitative approach to understand the reality that occurs, researchers want to show the parenting patterns used by mothers who perform two roles between a career outside the home and taking care of children in this case, which is seen how the mother educates in instilling Islamic religious values in children and is also assisted by a review of relevant literature. Data collection techniques carried out using interviews with relevant informants, interviews aim to get in-depth information. Based on the results of interviews in parenting career mothers teach Islamic religious values with a strategy of persuading and advising children according to what parents want to teach children and children must obey their parents' orders, this description of democratic parenting although different ways of implementing it still packs it in the important points of democratic parenting.